2015
DOI: 10.1016/j.imlet.2015.02.004
|View full text |Cite
|
Sign up to set email alerts
|

A re-evaluation of the role of B cells in protective immunity to Chlamydia infection

Abstract: Chlamydia trachomatis is the etiological agent of the most commonly reported bacterial sexual transmitted infection (STI) in North America and Europe. The control of Chlamydia infection is hindered by the asymptomatic nature of initial infection but the consequence of untreated infection seriously threatens the reproductive health of young women. Unfortunately, there is no licensed vaccine for Chlamydia vaccine, in part due to our incomplete understanding of the immune response to Chlamydia urogenital infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 78 publications
0
30
1
Order By: Relevance
“…B cell and antibody-mediated immunity against Chlamydia infection is not completely understood [38]. In 1997, Su et al demonstrated that B cell-deficient mice (μMT) cleared C. muridarium primary infections with normal kinetics of bacterial shedding from the genital tract but knockout mice were more susceptible to reinfection compared to wild type control mice [39].…”
Section: Immune Correlates Of Protective Immunity Against C Trachomatismentioning
confidence: 99%
“…B cell and antibody-mediated immunity against Chlamydia infection is not completely understood [38]. In 1997, Su et al demonstrated that B cell-deficient mice (μMT) cleared C. muridarium primary infections with normal kinetics of bacterial shedding from the genital tract but knockout mice were more susceptible to reinfection compared to wild type control mice [39].…”
Section: Immune Correlates Of Protective Immunity Against C Trachomatismentioning
confidence: 99%
“…By comparison, the antibodies present in sera of naturally infected koalas with clinical disease, were found not to have any neutralisation ability. Although it has previously been thought that antibodies predominantly bind to the surface exposed epitopes to enable the neutralisation [86], we found that antibodies targeting apparently internal epitopes, such as those in the conserved/membrane anchored regions of MOMP, could also effectively neutralise infectivity. One possible explanation for this is that, recent studies have shown that antibodies can be taken up inside the epithelial cells through FcRn mediated transport and thereby neutralise virus [72] and intracellular bacteria, like Chlamydia [73].…”
Section: Discussioncontrasting
confidence: 52%
“…CD4+ T cells as well as CD8+ T cells are found at the infection site against C. trachomatis infection in human and mouse models [86,87]. Antigen presenting cells (APC) are able to phagocytose chlamydial EBs, degrade chlamydial components into peptides and present them in conjunction with MHC class II to the CD4+ T cells.…”
Section: Immunity Against Chlamydiamentioning
confidence: 99%
“…In addition, recent studies have highlighted anti-chlamydial immune responses via protective tissue resident memory T-cell subsets in vaccinated mice, 48 and B cells enhancing Ag-specific CD4 + T-cell priming upon infection. 56,57 In the context of a future Chlamydia vaccine and a possible role for CPAF, there is no consensus as to whether the desired outcome is a reduction in infectivity/transmission or a reduction in the clinically relevant chronic pathologies. Along with the reduction in bacterial shedding (around second week), we have previously demonstrated superior protection against upper reproductive pathologies with the rCPAF regimen, 11 including protection against infertility induced following repeated chlamydial challenge.…”
Section: Discussionmentioning
confidence: 99%